AQUINAS'S ARGUMENT AGAINST SELF-HATRED - Green, Keith (Journal of religious ethics, 2007)
Aquinas's argument against the possibility of genuine self-hatred runs counter to modern intuitions about self-hatred as an explanatorily central notion in psychology, and as an effect of alienation. Aquinas's argument does not deny that persons experience hatred for themselves. It can be read either as the claim that the self-hater mistakes what she feels toward herself as hatred, or that, though she hates what she believes is her “self,” she actually hates only traits of herself. I argue that the argument fails on both readings. The first reading entails that all passions are really self-love, and so is incompatible with Aquinas's own “cognitivist” view of what it is that distinguishes specific passions in experience. The second reading entails that persons have no phenomenal access to “self,” rendering self-reference—how it is that the self can be an intentional object of conscious mental states—a mystery. Augustine's claim, which Aquinas accepts on authority, that all sin originates in inordinate self-love seems to entail the impossibility of genuine self-hatred because both thinkers fail to distinguish between two distinct forms of self-love: amor concupiscentiae and amor benevolentiae.